PENGARUH TEMAN SEBAYA DAN LINGKUNGAN BELAJAR TERHADAP PRESTASI BELAJAR IPS SISWA KELAS VIII SMP NEGERI 7 PEMATANGSIANTAR TAHUN AJARAN 2023/2024 - Chicy Viola Rahmawati Manurung; Sotarduga Sihombing (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The problem in this research is the low learning achievement of students in social studies subjects. This research aims to determine the influence of peers and the learning environment on the learning achievement of class VIII students at SMP Negeri 7 Pematangsiantar. The variables in this research are peers and the learning environment as independent variables and learning achievement as the dependent variable.This type of research is descriptive quantitative research, with the population being all students in grades VIII-4 to VIII-8 at SMP Negeri 7 Pematangsiantar with a total of 160 students and the research sample taken was 115 students selected through random sampling techniques. Data collection techniques were carried out through observation and questionnaires, while the data analysis techniques used were validity test, reliability test, normality test, normal distribution test, multiple linear regression test, t test, f test and coefficient of determination test.From the results of data analysis using the Excel application, it is known that there is a significant influence between peers on the learning achievement of class VIII students at SMP Negeri 7 Pematangsiantar, with the tcount result being 5.3504>ttable 1.658, then, there is a significant influence between the learning environment on learning achievement, This is proven by the value of tcount of 5.7081>ttable 1.658, and it is concluded that H0 is rejected and Ha is accepted, this means that peer variables and the learning environment have an influence on the learning achievement of class VIII students at SMP Negeri 7 Pematangsiantar. Then there is a simultaneous or joint influence between peers and the learning environment on learning achievement, this can be seen from the Fcount value of 45.816 > Ftable 3.077. The R Square coefficient of determination test was found to be 0.449, which means that 44.9% of peer variables and the learning environment influence student achievement at SMP Negeri 7 Pematangsiantar.